Den, volume 3 ebook Children of fire. - Corben, Richard (Den, 2024)
The third volume presenting the long-out-print masterpiece Den, by fantasy legend Richard Corben!This special edition collects the third volume of the long out-of-print Den, and also features bonus material, art pages restored by long-time Corben collaborator José Villarrubia, re-lettered by Nate Piekos of Blambot, and an introduction by Matt Kindt, all presented in a gorgeous hardcover with a dust jacket.Aliens flee their planet after a monster attack and crash-land near a sorcerer’s castle in Neverwhere. They must fight for survival and protect their egg and future kin at all costs from the many beasts, pirates, and other threats to their safety.Den: Children of Fire is the next book in a series of deluxe graphic novels from renowned creator Richard Corben’s library to be published by Dark Horse Comics.FOR MATURE READERS“The artist I most want to aspire to is Richard Corben. His style is visual and it tells the story just as you see it... ...my favorite is Corben. I love everything he does, I love his stuff ...he’s an amazing artist.”—Guillermo del Toro"Richard Corben stands among us like an extraterrestrial peak. He has sat in his throne a long time, above the moving and multi-colored field of world comics, like an effigy of the leader, a strange monolith, a sublime visitor, a solitary enigma"—Moebius“Mr. Richard Corben... a genuine giant of his chosen medium.”—Alan MooreWell known for his legendary fantasy underground masterpieces published by Fantagor Press as well as Heavy Metal, Richard Corben’s work has been recognized internationally having been awarded one of the most prestigious recognitions in comics literature the Grand Prix at Angoulême as well having been inducted into the Will Eisner Award Hall of Fame.